Gender Self-Confidence as a Protective Factor for Suicide Risk: Analysis of the Sample of Lithuanian Men - Grigienė, Dovile; Skruibis, Paulius; Dadašev, Said; Rimkevičienė, Jurgita; Gailienė, Danute (Frontiers in Psychology, 2022)
Background: Along with other suicide risk factors, masculinity has been analysed as an important subject for suicidal behaviour in men. This study examines masculinity as a gender self-confidence which is the intensity of an individual’s belief that he meets his personal standards for masculinity. We use Hoffman and her colleague’s concept, which provides two theoretical constructs as elements of gender self-confidence: gender self-definition and gender self-acceptance. Gender self-definition relates to how salient masculinity in one’s identity is; gender self-acceptance relates to how positively one views his own masculinity. Methods: The quantitative research approach was applied in the study. The survey with a nonprobability quota sampling design was implemented to collect the data. The sample consisted of 562 Lithuanian men from various age groups and regions. The age of participants varied from 18 to 92 years (M = 42.99, SD = 17.18). 40.9% of men were from cities, 28.1% from towns and 30.8% from rural locations. We used the Hoffman Gender Scale to measure gender self-definition and gender self-acceptance. Suicide risk was estimated with the Suicide Behavior Questionnaire – Revised. Patient Health Questionnaire-2 was used to measure depression symptoms as a controlled variable. Statistical analysis of regression and moderation was used to test the hypothesis. Results: Higher gender self-definition and higher gender self-acceptance were associated with a lower suicide risk. The moderation analysis showed that in men with relatively low gender self-definition the effect of gender self-acceptance on suicidality was larger than in men with high or moderate gender self-definition. Discussion: We conclude that a stronger gender self-confidence is an important protective factor in male suicide risk. Both, a smaller part of masculinity in one’s identity and a negative view about one’s masculinity have a cumulative effect on an increased suicide risk. The findings have been discussed in accordance with the theories that explain suicidal behaviour through the lenses of self-concept.